Cytokines Involved in the Systemic Inflammatory Response Induced by Exposure to Particulate Matter Air Pollutants (PM10) - van EEDEN, STEPHAN F; TAN, WAN C; SUWA, TATSUSHI; MUKAE, HIROSHI; TERASHIMA, TAKESHI; FUJII, TAKESHI; QUI, DIWEN; VINCENT, RENAUD; HOGG, JAMES C (American journal of respiratory and critical care medicine, 2001)
Elevated levels of ambient particulate matter (PM(10)) have been associated with increased cardiopulmonary morbidity and mortality. We previously showed that the deposition of particles in the lung induces a systemic inflammatory response that includes stimulation of the bone marrow. This marrow response is related to mediators released by alveolar macrophages (AM) and in this study we measured cytokines produced by human AM exposed to ambient particles of different composition and size. Identified cytokines were also measured in the circulation of healthy young subjects exposed to air pollutants during the 1997 Southeast Asian forest fires. Human AM were incubated with particle suspensions of residual oil fly ash (ROFA), ambient urban particles (EHC 93), inert carbon particles, and latex particles of different sizes (0.1, 1, and 10 microm) and concentrations for 24 h. Tumor necrosis factor-alpha (TNF-alpha) increases in a dose-dependent manner when AM were exposed to EHC 93 particles (p < 0.02). The TNF response of AM exposed to different sizes of latex particles was similar. The latex (158 +/- 31%), inert carbon (179 +/- 32%), and ROFA (216 +/- 34%) particles all show a similar maximum TNF response (percent change from baseline) whereas EHC 93 (1,020 +/- 212%, p < 0.05) showed a greater maximum response that was similar to lipopolysaccharide (LPS) 1 microg/ml (812 +/- 320%). Macrophages incubated with an optimal dose of EHC 93 particles (0.1 mg/ml) also produce a broad spectrum of other proinflammatory cytokines, particularly interleukin (IL)-6 (p < 0.01), IL-1 beta (p < 0.05), macrophage inflammatory protein-1 alpha (MIP-1 alpha) (p < 0.05), and granulocyte macrophage colony-stimulating factor (GM-CSF) (p < 0.01) with no difference in concentrations of the anti-inflammatory cytokine IL-10 (p = NS). Circulating levels of IL-1 beta, IL-6, and GM-CSF were elevated in subjects exposed to high levels of PM(10) during an episode of acute air pollution. These results show that a range of different particles stimulate AM to produce proinflammatory cytokines and these cytokines are also present in the blood of subjects during an episode of acute atmospheric air pollution. We postulate that these cytokines induced a systemic response that has an important role in the pathogenesis of the cardiopulmonary adverse health effects associated with atmospheric pollution.